2020
DOI: 10.4110/in.2020.20.e21
|View full text |Cite
|
Sign up to set email alerts
|

TLR10 and Its Unique Anti-Inflammatory Properties and Potential Use as a Target in Therapeutics

Abstract: TLRs are pattern recognition receptors (PRRs) whose cytoplasmic signalling domain is similar to that of IL-1. The extracellular domain of TLRs serve as the binding site of pathogen associated molecular patterns. TLRs are found on both plasma and endosomal membranes and they mainly exert their function by activating genes which lead to production of inflammatory factors. The latest TLR to be discovered, TLR10 is a unique TLR which exhibit anti-inflammatory properties. TLR10 is found on the plasma membrane with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 50 publications
0
51
0
1
Order By: Relevance
“…CD22 is an important drug target for ameliorating autoimmune diseases and acute lymphoblastic leukemia 36 , 37 . TLR-10 is a pattern recognition receptor with anti-inflammatory properties 38 . Kopp et al found that TLRs are associated with colorectal cancer via nuclear transcription factor-κB-initiated transcription of inflammatory genes 39 .…”
Section: Discussionmentioning
confidence: 99%
“…CD22 is an important drug target for ameliorating autoimmune diseases and acute lymphoblastic leukemia 36 , 37 . TLR-10 is a pattern recognition receptor with anti-inflammatory properties 38 . Kopp et al found that TLRs are associated with colorectal cancer via nuclear transcription factor-κB-initiated transcription of inflammatory genes 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The function of TLR10 is inhibitory, whereas TLR1, TLR2 and TLR6 promote the innate immune responses. 15 A recent study evaluated whether TLR10 modulates the induction of immunity induced by BCG. 16 The figure 0 was replaced by 1 in analyses to allow the p value calculation.…”
Section: Discussionmentioning
confidence: 99%
“…TLR1, TLR6 and TLR10 act as co‐receptors for TLR2, and therefore, these four TLRs are called as a TLR2 subfamily. The function of TLR10 is inhibitory, whereas TLR1, TLR2 and TLR6 promote the innate immune responses 15 . A recent study evaluated whether TLR10 modulates the induction of immunity induced by BCG 16 .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, TLR10, another member of the TLR2 subfamily, has high structural homology with TLR1 and TLR6. It can homo-dimerize or heterodimerize with TLR1 and TLR2 (Fore et al 2020 ; Xiang et al 2020 ). Nevertheless, the research on the ligand recognition, signal pathway, and biological function of TLR10 is not comprehensive yet.…”
Section: Lipoprotein Is the Predominant Ligand For The Tlr2 Subfamilymentioning
confidence: 99%